2006
DOI: 10.1063/1.2207502
|View full text |Cite
|
Sign up to set email alerts
|

Field-effect modulation of the transport properties of nondoped SrTiO3

Abstract: We have fabricated SrTiO3 (100) single crystal field-effect transistors with amorphous and epitaxial CaHfO3 gate insulator layers. The devices with amorphous insulator layers showed nearly temperature independent behavior. The transistors with epitaxial interfaces exhibited a large improvement over the amorphous devices. The field-effect mobility was found to increase at low temperature, reaching 35cm2∕Vs at 50K. This result shows that the carriers accumulated by the field effect on the SrTiO3 side of the gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…If our FET is compared with other perovskite-based FETs where hetero-interfaces between two single-crystalline perovskite oxides were employed: DyScO 3 /STO and CaHfO 3 /STO interfaces, µ FE , and I on /I off are 40 times and an order higher in our FET, respectively. 20,21 These performances of our FET are also comparable to the best performances of In 2 O 3 :ZnO-based FET. 22 The reasons for such high device performance can be attributed to the material properties of BSO, the use of epitaxial gate dielectric, the quality of the LIO/BLSO interface, and the possibility of the formation of two dimensional electron gas (2DEG) at the LIO/BLSO interface resulting from its polar discontinuity.…”
supporting
confidence: 67%
“…If our FET is compared with other perovskite-based FETs where hetero-interfaces between two single-crystalline perovskite oxides were employed: DyScO 3 /STO and CaHfO 3 /STO interfaces, µ FE , and I on /I off are 40 times and an order higher in our FET, respectively. 20,21 These performances of our FET are also comparable to the best performances of In 2 O 3 :ZnO-based FET. 22 The reasons for such high device performance can be attributed to the material properties of BSO, the use of epitaxial gate dielectric, the quality of the LIO/BLSO interface, and the possibility of the formation of two dimensional electron gas (2DEG) at the LIO/BLSO interface resulting from its polar discontinuity.…”
supporting
confidence: 67%
“…An alternative approach has shown that two dimensional electron gas can be created at SrTiO 3 /LaAlO 3 hetero-interface by a charge-transfer due to a polar discontinuity [9,10,11,12,13,14] or possible oxygen defects [15]. This electronically tailored interface was found to be superconducting as in the bulk material [14].Recently the performance of SrTiO 3 FET has been drastically improved [16,17] by overcoming the contacts and interface problems. These new devices showed metallic behavior down to 7 K [17].…”
mentioning
confidence: 99%
“…Recently the performance of SrTiO 3 FET has been drastically improved [16,17] by overcoming the contacts and interface problems. These new devices showed metallic behavior down to 7 K [17].…”
mentioning
confidence: 99%
“…However, it is difficult to make even metallic conduction at low temperature by a conventional MISFET. 11,33,34) High-density charge carrier by an EDLT overcomes the difficulty of obtaining the metallic state, and we succeeded for the first time to obtain a superconducting state that emerged from an insulating state by the electric field effect. By applying a gate bias of above 2.5 V, a SrTiO 3 EDLT with a PEO electrolyte shows metallic conduction down to 2 K. The sheet resistance decreases by two orders of magnitude with decreasing temperature because of the large increase in electron mobility at low temperature.…”
Section: Superconductivity and Low-temperature Transport Propertiesmentioning
confidence: 99%